Penumbuhan Film Tipis Ti1-xCoxO2 Dengan Metode MOCVD - Horasdia Saragih; Mersi Kurniati; Akhiruddin Maddu; Pepen Arifin; Moehamad Barmawi (Institut Teknologi Bandung, 2004)
The Ti1-xCoxO2 thin films have been successfully deposited on Silicon (Si) substrates by metalorganic chemical vapor deposition (MOCVD). The Ti1-xCoxO2 thin films with x = 0 is grown at deposition temperature of 450oC with argon and oxygen flow rate of 100 sccm and 60 sccm, respectively. The deposited film has a single orientation of (213)-anatase. The films consist of nanometer size of columnar grains. The growth rate was increased with increasing Co content and therefore the grains become larger. Generally, the crystal structure of films was affected by Co atom concentrations, however at temperature deposition of 450oC and argon flow rate of 70 sccm, the film has the initial structure of (213)-anatase and co-exist with (301)-anatase which is not dominant. The film thickness is about of 0,9 Î¼m for an area of 3x3 cm2.